2014
DOI: 10.1016/j.ihj.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Congenital anomalous/aberrant systemic artery to pulmonary venous fistula: Closure with vascular plugs & coil embolization

Abstract: A 7-month-old girl with failure to thrive, who, on clinical and diagnostic evaluation [echocardiography & CT angiography] to rule out congenital heart disease, revealed a rare vascular anomaly called systemic artery to pulmonary venous fistula. In our case, there was dual abnormal supply to the entire left lung as(1) anomalous supply by normal systemic artery [internal mammary artery](2) and an aberrant feeder vessel from the abdominal aorta. Left Lung had normal bronchial connections and normal pulmonary vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Congenital AVF arising from thoracic aorta and draining into the left inferior pulmonary vein without lung sequestration is an extremely rare malformation. [1,6,7] Pernot et al reported a case in which left lobectomy showed a fistula arising from the aorta and a pulmonary vein, associated with absence of a branch of the pulmonary artery. [8] Dahiya et al reported a fistula between the abdominal aorta and right inferior pulmonary vein in an asymptomatic 25-year-old man; surgical ligation performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Congenital AVF arising from thoracic aorta and draining into the left inferior pulmonary vein without lung sequestration is an extremely rare malformation. [1,6,7] Pernot et al reported a case in which left lobectomy showed a fistula arising from the aorta and a pulmonary vein, associated with absence of a branch of the pulmonary artery. [8] Dahiya et al reported a fistula between the abdominal aorta and right inferior pulmonary vein in an asymptomatic 25-year-old man; surgical ligation performed.…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which AVF is clinically and echocardiographically suspected, multislice CTA is an appropriate imaging method to confirm diagnosis and select therapy modality. [4,7] In addition, cardiac catheterization and angiography is necessary for both diagnosis and intervention procedures. [3] Brühlmann et al described the first transarterial therapeutic embolization of systemic arterialization of the lung without sequestration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac CT is helpful when echocardiography fails to identify the cause of abnormal pressure variation in cardiac chambers. Cardiac CT can also diagnose the presence of lung sequestration,1 which decides subsequent disease management 2. Systemic branches from the aorta supply the primitive lung and are replaced by the pulmonary arteries (from the 6th aortic arch) around the fifth week, failure of which (due to pulmonary oligaemia) is proposed as the theory for pulmonary arterialisation (pseudosequestration) 3…”
Section: Descriptionmentioning
confidence: 99%